Prevalence of advanced colorectal neoplasm is higher in liver transplant recipients - Kang, Eun Ae; Koh, Seong-Joon; Kim, Ji Won; Lee, Kook Lae; Im, Jong Pil; Kim, Joo Sung; Kim, Byeong Gwan (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Patients with liver transplantation are at increased risk of developing new malignancy because of the prolonged immunosuppression after transplantation. The aims of this study were to investigate whether advanced colorectal neoplasms occurs more in liver transplant recipients compared to healthy individuals and to evaluate the effect of immunosuppression on advanced colorectal neoplasia. Materials and Methods: This was a retrospective, single-centered, case-control study. We reviewed 348 liver transplant patients who had undergone a colonoscopy after liver transplantation from 1991 to 2012. Healthy controls from asymptomatic individuals who had undergone colonoscopy for screening purposes were randomly selected and reviewed. Results: Advanced colorectal neoplasms were identified in 17 of the 348 patients (4.9%). The risk of advanced colorectal neoplasia was 3.6 times greater in liver transplant patients (odds ratio [OR] 3.578; 95% confidence interval [CI] 1.578-8.115; p=0.001). The risk of developing colon cancer was 8.4 times higher in transplant patients (OR 8.416; 95% CI 1.808-39.172; p=0.001). Conclusion: Liver transplant recipients were at a high risk of colorectal cancer. Therefore, colonoscopy surveillance after liver transplantation is recommended. Immunosuppressive therapy could facilitate carcinogenesis. Cite this article as: Kang EA, Koh SJ, Kim JW, et al. Prevalence of advanced colorectal neoplasm is higher in liver transplant recipients. Turk J Gastroenterol 2018; 29: 316-24.